Mathematics of Business and Finance/Selected Tables for Business and Financial Calculations (Book). - Zempel, Arnold (The Accounting Review, 1938)
Reviews two books. "Mathematics of Business and Finance," and "Selected Tables for Business and Financial Calculations," by William S. Schlauch and Theodore Lang.